PENDIDIKAN DAN PELATIHAN VOKASI UNTUK MENCIPTAKAN LAPANGAN PEKERJAAN - ARISMAN PARHUSIP (JURNAL ILMIAH KOHESI, 2022)
This research is motivated by the importance of optimizing the quality of human resources, especially for the workforce. The quality of human resources can be improved by training. Medan City Government through the Center for Vocational Training & Productivity (BBPVP) Medan. BBPVP is a competency-based training program, knowing the training strategy is expected to develop BBPVP in a better direction. In addition, knowing the strategy in BBPVP is expected to improve the quality of human resources so that they can meet job opportunities. Based on the description above, the researchers will formulate the following problems: How can the Center for Vocational Training & Productivity of Medan City create community jobs. This study uses a qualitative approach with a descriptive type of research. The process of collecting data using the methods of observation, interviews, and documentation. The data analysis technique in this research is data reduction, data presentation, and conclusion drawing. The conclusion of this research is: Vocational & Productivity Training is very helpful to create job opportunities for alumni. This is because their education system is very good and well planned, starting from offering training programs to completion, even until the alumni work/open businesses. Job opportunities are also created from training at other Job Training Centers because there are job fairs and job skills that are held once every year, the implementation of the Inter-Regional Inter-Working Program (AKAD) and Inter-Overseas Inter-Working (AKAN) program